Islamic Education in the Digital Era: Pedagogical Competence, Technology Acceptance, and Managerial Supervision - Indra Azwar Mawardi; Ahmad Sukandar (CV. Media Digital Publikasi Indonesia, 2025)
The rapid advancement of digital technology in the 21st century has significantly influenced the landscape of education, including Islamic Religious Education (PAI). Teachers are expected not only to master basic knowledge but also to integrate critical thinking, creativity, and adaptability into their instructional practices. This study aims to analyze the implementation of digital transformation in Islamic education through the lens of pedagogical competence, managerial supervision, and cultural adaptation. A qualitative approach with a case study design was employed, focusing on purposively selected institutions that demonstrate initiatives in digital Islamic learning. Data were collected through literature review, document analysis, and triangulation with empirical findings from recent studies. The researcher acted as the primary instrument, supported by systematic coding and thematic matrices, while trustworthiness was ensured using credibility, transferability, dependability, and confirmability criteria. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the integration of the TPACK (Technological Pedagogical Content Knowledge) and TAMISE (Technology Acceptance Model in Islamic Education) frameworks significantly improved the effectiveness of PAI learning. Student engagement increased by 41% through augmented reality and gamification, while 89% of teachers successfully developed adaptive learning modules using AI-based tools. The MTDPI (Model Transformasi Digital Pendidikan Islam), which incorporates a maqāṣid shariah-based technocultural foundation, hybrid pedagogy, and a scholar-technocrat ecosystem, proved effective in aligning innovation with Islamic values. However, implementation challenges persist. Only 29% of madrasahs in rural areas have adequate internet access compared to 89% in urban areas, highlighting infrastructural inequality. Moreover, 34% of senior teachers resisted the use of gamification, citing concerns over the sacredness of Islamic knowledge. Governance issues, particularly the absence of content verification mechanisms, were also identified as barriers. Nonetheless, blockchain-based evaluation systems demonstrated potential by reducing verification time from seven days to two hours while ensuring content authenticity.